Optimization of Antibacterial Activity in Tibetan Swine α-Helix Peptide TP by Site-Directed Mutagenesis - Li, Guoyu; Yuan, Xiaojie; Chen, Hongyu; Li, Bowen; Shao, Changxuan; Zhu, Yongjie; Lai, Zhenheng; Shan, Anshan (Frontiers in Microbiology, 2022)
Antimicrobial peptides (AMPs) have attracted extensive attention because of their broad-spectrum antibacterial activity and low level of induced bacterial resistance. However, the development of some natural AMPs does not consider the perfect balance of structural characteristics, resulting in some empirical and controversial practices still existing. To further explore and complete the relationship between parameters and function of α-helix peptide, in this study, the natural antimicrobial peptide TP secreted from Bacillus strain of Tibetan pigs was selected as a template to investigate the effect of systematic mutations in the hydrogen bond formation site of the α-helical antimicrobial peptide on the activity and cell selectivity of the antimicrobial peptide. The target peptide TP(i+4) 1&2&5 with modification of two pairs of positively charged amino acids and a pair of hydrophobic amino acids showed excellent antibacterial ability and the best selectivity index (SI = 64) in vitro. At the same time, TP(i+4) 1&2&5 remained active in the presence of physiological salts and serum. The results of fluorescence, flow cytometry, and electron microscopy showed that the optimized sequences showed good antibacterial activity by membrane infiltration and membrane destruction. The potential of TP(i+4) 1&2&5 in vivo was tested in a mouse peritonitis model. Organ bacterial loads in the liver, kidney, spleen, and lungs of mice treated with TP(i+4) 1&2&5 were significantly lower compared to the infected group (p < 0.05). Overall, these findings contribute to the design and optimization of antimicrobial peptides with high activity and low toxicity and may accelerate the clinical application of antimicrobial peptides.